The Influence of STEAM-Based Project-Based Learning on Student Creativity at Pena Surabaya Homeschooling - Umma, Farah Khosravi; Artha, I Ketut Atmaja Johny; Yulianingsih, Wiwin (research, training and philanthropy institution Natural Aceh, 2024)
Humans need to continue to innovate and develop by the progress of the times. Therefore, education is an essential pillar for producing the next generation, which will face challenges in the era of the Industrial Revolution. Their critical thinking skills, creativity, and self-development are very important to protect students from fierce competition. Therefore, the learning model is essential in forming students to produce a reliable generation. Science, Technology, Engineering, Art, and Mathematics (STEAM) is the right choice for students to train in creativity. This study aims to determine the creativity abilities of students at Homeschooling Pena Surabaya. The method used is experimental quantitative with 18 students as samples (total sampling)—data collection techniques through questionnaires, documentation, and observation. The statistical results state that a significant influence between STEAM-based Project Based Learning (PBL) learning on creativity, known from the calculated r, is greater than the table r (10.096˃2.131). The maximum post-test score is 100 for one person and is included in the